Perceived Relative Distance Depends on the Size Ratio of Targets in Photographs. (March 2013) - Takezawa, Tomomi
Focussing on the relationship between distance perception in photographs and the image sizes of the targets on the photographic surface, it is shown that the perceived relative distances between near and far targets depends on their image size ratios. Two targets of the same physical size were placed at fixed distances from each other and their photographs were taken. The image size of the near target was kept constant and the size ratio of the far target image was controlled by manipulating the camera-to-target distances appropriate to the focal lengths of the lenses. Forty undergraduates viewed the photographs and placed an actual target at the same relative distance to the near target as seen in the photographs. The results showed that the smaller the size ratios, the larger the perceived relative distances even when the actual relative distances remained the same. In addition, the perceived relative distance was smaller than the actual relative distance even in the condition where the retinal sizes of the two target images matched the retinal sizes of the actual targets seen from the camera position. However, it was found that the perceived relative distance could approximate the actual relative distance if the size ratio were further reduced.